2019
DOI: 10.1101/841007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human papillomavirus 16 E6 and E7 synergistically repress innate immune gene transcription

Abstract: 12Human papillomaviruses are causative agents in 5% of all cancers, including the majority of ano-13 genital and oropharyngeal cancers. Downregulation of innate immune genes (IIGs) by HPV to 14 promote the viral life cycle is well documented; E6 and E7 are known repressors of these genes. 15More recently we demonstrated that E2 could also repress IIGs. These studies have been carried 16 out in cells over-expressing the viral proteins and to further investigate the role of individual viral 17 proteins in this r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…To investigate the role of WRN during the viral life cycle, we exploited our N/Tert-1 model. N/Tert-1 are hTERT immortalized human foreskin keratinocytes, and we generated cell lines containing HPV16, N/Tert-1+HPV16 ( 46 48 , 53 ). This system has the direct advantage of being able to manipulate control cells (N/Tert-1) without the viral genome but with the same genetic lesions as the N/Tert-1+HPV16 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of WRN during the viral life cycle, we exploited our N/Tert-1 model. N/Tert-1 are hTERT immortalized human foreskin keratinocytes, and we generated cell lines containing HPV16, N/Tert-1+HPV16 ( 46 48 , 53 ). This system has the direct advantage of being able to manipulate control cells (N/Tert-1) without the viral genome but with the same genetic lesions as the N/Tert-1+HPV16 cells.…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated whether the transcriptional reprograming of N/Tert-1 cells carried out by HPV16 oncogenes alone could sensitize cells to estrogen and attenuate cellular growth. To do this we expressed E6 or E7 or E6+E7 in N/Tert-1 cells and further compared these cells to those expressing the full HPV16 genome (N/Tert-1+HPV16); these E6, E7, and E6+E7 cell lines were generated using retroviral delivery and have been described previously(26, 52). Figure 6A demonstrates again that in N/Tert-1 control cells, estrogen treatment does not attenuate cellular growth (Figure 6Ai) but the presence of the entire HPV16 genome promotes such attenuation (Figure 6Aii).…”
Section: Resultsmentioning
confidence: 99%
“…UMSCC104 (Millipore), and UMSCC152 (ATCC) cells were grown in Eagle’s Minimum Essential Medium (EMEM, Invitrogen) supplemented with non-essential amino acids (NEAA, Gibco) and 10% charcoal stripped fetal bovine serum. N/Tert-1 cells and all derived cell lines, as well as HTK+HPV16 cells (a generous gift from Dr. Craig Meyers, UPenn, Hershey) have been describe previously(24, 25, 52, 59) and were maintained in keratinocyte-serum free medium (K-SFM, Invitrogen), supplemented with a 1% (vol/vol) penicillin-streptomycin mixture (ThermoFisher Scientific). All N/Tert-1 cells were also supplemented with 4 μg/ml hygromycin B (Millipore Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…These studies employed overexpression of viral proteins, and monitored their effect on the cell and the DDR pathway. We recently reported that HPV16 activates the DDR in human keratinocytes irrespective of the expression of E6 and E7 ( Figure 4 ) [ 46 ]. This was done by introducing stop codons into the E6 and E7 genes (individually and combined) in the full HPV16 genome and generating N/Tert-1 (human foreskin keratinocytes immortalized by telomerase) cells containing wild type and mutant genomes.…”
Section: The Ddr During the Hpv Life Cyclementioning
confidence: 99%